The economic importance of the peanuts production chain - Neves, Fabiano Pinto [UNESP]; Leite, Alisson Rodolfo [UNESP]; Mantovani, Leandro Paloma [UNESP]; da Silva, Celso [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; De Oliveira, Sandra Cristina [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2023)
The importance and economic representativeness of the peanut production chain has grown exponentially in recent years, tending to gain more market share. Background: The study had as its theme the question: What is the economic, technological, social and environmental relevance of the peanut production chain for Brazil? Objective: Conduct a survey of information and data that allow inferring the economic, social and environmental importance of the peanut production chain for Brazil in the global scenario. Methods: The methodology applied was exploratory research ad hoc in exploratory theoretical essay of qualitative approach, and analytical descriptive in the report of the findings. Results: Exports grow on a logarithmic scale, in 2020 it had revenues of US$ 427.8 million. The sector generates 42 thousand jobs, and the culture makes it possible to meet social and environmental demands. Conclusions: The adoption of technologies and the improvement of production methods are essential for the continuous progress of the sector with the creation of jobs and the adhesion of new producers, with an increasingly sustainable production, with less environmental impact and reduction of fertilizer waste, with expansion of the productive capacity per planted bushel.
Keywords: Development; Economic Impact; Exports; SDGs; Technology